Learning from improvisation in New Ventures - Juan Wu; Felix Arndt; Hongjia Ma; Paul Hughes; Sisi Tang (Journal of Innovation & Knowledge (JIK), 2023)
The rapid pace of digitalization forces new ventures to cope with external changes they cannot foresee. Improvisation is a crucial way for companies to respond effectively to sudden changes. However, the mechanisms underlying the improvisation-performance link are not fully understood. This paper focuses on how improvisation affects a firm's performance. We identify two mediators for this relationship: entrepreneurial learning and routines. Our sample includes 243 new ventures in China. The results of structural equation modelling show that learning from improvisation in start-ups contributes to establishing new routines that serve as drivers of firm performance. We discuss the implications for practice and future research.
Keywords: M10; M13; 650; Entrepreneurial learning; Entrepreneurship; Improvisation; New venture performance; Routine